ABON IKAN SOLUSI USAHA KECIL YANG MENGUNTUNGKAN DAN BERKELANJUTAN - Dewi Puspita; Mardiana Mardiana; Nindy Cahya Ningsih; Sri Dhita Aulia; Dwi Utami Putri (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The community service program in Lais Village, Dondo District, Tolitoli Regency was carried out to enhance community skills in processing fish into value-added shredded fish (abon) products. The region has abundant fish resources, but utilization remains limited to selling fresh fish at low prices with a high risk of spoilage. The program applied methods such as socialization, technical training, and business management assistance. The results showed significant improvements in participants’ technical skills in fish processing, more hygienic packaging practices, and a better understanding of cost calculation and marketing strategies. The shredded fish produced had good taste, a shelf life of up to two months without preservatives, and strong potential for both traditional and digital marketing. The program provided positive socio-economic impacts by creating additional household income opportunities and fostering community self-reliance. With government policy support, abundant raw material availability, and increasing consumer demand for practical food, shredded fish products have strong potential to develop into sustainable and competitive small-scale businesses.